The Impact of Techno-stressor on Job Performance with Burnout as Mediator for Studies in the Public Sector (International Journal of Scientific Research and Management (IJSRM), 2023)
The public sector is currently aggressively digitizing by adopting various technologies. The application of technology can have both positive and negative results. The adverse effects of technology need to be studied as a form of mitigation dealing with failures in implementing technology in the workplace. This study aims to analyze the direct and indirect effects of stress caused by technology (technostress) on job performance, both task and contextual, with burnout as mediation. With a quantitative approach that uses primary data, this research data was collected through an online survey. Data collection was carried out purposively in the public sector, namely the Central Statistics Agency (BPS), and 181 eligible samples were obtained. Data analysis used the Structural Equation Modeling Partial Least Square (PLS-SEM) method. The results showed that the techno-stressor positively and significantly affected burnout. Likewise, burnout also has a negative and significant impact on task and contextual performance. The development of techno-stressor on task performance and contextual performance has the opposite direction to the hypothesis. Although the results of the effect on task performance are not significant, the focus of this different hypothesis is a confirmation that stress is not the only effect. Still, if technostress is appropriately managed, it can produce positive results. Furthermore, the influence of the techno-stressor has a negative and significant impact on task performance and contextual performance when it is mediated by burnout. This result shows that the mediating role of burnout greatly determines whether this technological stress will hurt task performance and contextual performance.